The Relationships of Sleep Duration and Inconsistency With the Athletic Performance of Collegiate Soft Tennis Players - Han, Tianfang; Wang, Wenjuan; Kuroda, Yuta; Mizuno, Masao (Frontiers in Psychology, 2022)
We evaluated the relationships of daily sleep duration and inconsistency with soft tennis competitive performance among 15 healthy collegiate soft tennis players (13 male, 2 female, mean age = 19.7 ± 0.8 years, height = 170.8 ± 7.3 cm, weight = 60.3 ± 5.6 kg, soft tennis experience = 8.7 ± 2.0 years). Sleep duration and inconsistency were determined by a 50-day sleep diary, which recorded sleep and wake times of sleep. Soft tennis athletic performance was evaluated by a service and baseline stroke accuracy test and the spider run test. Mean sleep duration was 7.4 ± 1.7 h. No correlation was found between long-term mean sleep duration and athletic performance. But inconsistency in sleep duration (SD of sleep duration) was inversely correlated with service score after controlling for soft tennis experience and sex (r = −0.56, p = 0.046). There was no significant relationship between sleep inconsistency and other athletic performance. This result indicates that reducing the instability of sleep duration (i.e., sleep regular hours) in the long-term may have a positive effect on soft tennis players’ service performance. Although participants’ current mean sleep duration (7.4 h) was not as sufficient as the recommendation in sleep extension experiments (9–10 h), it revealed the importance for athletes to maintain regular sleep in daily life.